Information and communication technologies in education, research, and industrial applications : 12th International Conference, ICTERI 2016, Kyiv, Ukraine, June 21-24, 2016, Revised selected papers /: 12th International Conference, ICTERI 2016, Kyiv, Ukraine, June 21-24, 2016, Revised selected papers. (2017) - Unknown
No abstract available